On Bornivorous Set - Al-Basri, Fatima Kamil Majeed (Al-Qadisiyah Journal of Pure Science, 2017)
In this paper, we introduce the concept of the bornivorous set and its properties to construct bornological topological space .Also, we introduce and study the properties related to this concepts like bornological base, bornological subbase , bornological closure set, bornological interior set, bornological frontier set and bornological subspace